The Value of Duodenal Biopsies in the Evaluation of Megaloblastic Anemia - Nasrin, Nisha N.; Shanmugasundaram, Sakthisankari; Kartikayan, R. K. (Journal of Laboratory Physicians, 2021)
Introduction Megaloblastic anemia is one of the common causes of anemia in India. Duodenal biopsies are routinely performed in the investigation of megaloblastic anemia. The present study was undertaken to analyze the value of duodenal biopsy in megaloblastic anemia and to correlate endoscopic findings with biopsy. As a secondary aim, the study has also analyzed the hematological profile and vitamin B12 and folate status of these patients.Materials and Methods All the cases of megaloblastic anemia with bone marrow studies diagnosed at PSG Institute of Medical Sciences and Research during the two year period from January 2016 to December 2017 were retrieved. Clinical and laboratory findings (serum vitamin B12 and folate levels) and endoscopic findings were retrieved from hospital records of the patients. Duodenal biopsies of these patients reported in the histopathology department were retrieved and reviewed. Statistical analysis was done using SPSS software 20.0.Results There were 93 cases of megaloblastic anemia diagnosed on bone marrow biopsies. Tropical sprue was diagnosed in 49.5% of cases, followed by intraepithelial lymphocytosis (17.2%), peptic duodenitis (17.2%), and no significant pathology in 16% of cases. Pancytopenia was present in 54.8% of cases. Isolated vitamin B12 deficiency including low levels was present in 48.38% and folate deficiency was seen in 4.3% cases; 34.48% cases had both vitamin B12 and folate deficiency.Conclusion The incidence of tropical sprue in megaloblastic anemia is 49.5% in the study. Duodenal biopsy is valuable in the work up of megaloblastic anemia, irrespective of the endoscopic changes in identifying the etiology.
Keywords: megaloblastic anemia; tropical sprue; vitamin B12; folate; pancytopenia; intraepithelial lymphocytosis